Who teaches children to forage? Exploring the primacy of child-to-child teaching among Hadza and BaYaka Hunter-Gatherers of Tanzania and Congo - Lew-Levy, Sheina; Kissler, Stephen M.; Boyette, Adam H.; Crittenden, Alyssa N.; Mabulla, Ibrahim A.; Hewlett, Barry S. (Evolution and human behavior, 2020)
Teaching is cross-culturally widespread but few studies have considered children as teachers as well as learners. This is surprising, since forager children spend much of their time playing and foraging in child-only groups, and thus, have access to many potential child teachers. Using the Social Relations Model, we examined the prevalence of child-to-child teaching using focal follow data from 35 Hadza and 38 BaYaka 3- to 18-year-olds. We investigated the effect of age, sex and kinship on the teaching of subsistence skills. We found that child-to-child teaching was more frequent than adult-child teaching. Additionally, children taught more with age, teaching was more likely to occur within same-sex versus opposite-sex dyads, and close kin were more likely to teach than non-kin. The Hadza and BaYaka also showed distinct learning patterns; teaching was more likely to occur between sibling dyads among the Hadza than among the BaYaka, and a multistage learning model where younger children learn from peers, and older children from adults, was evident for the BaYaka, but not for the Hadza. We attribute these differences to subsistence and settlement patterns. These findings highlight the role of children in the intergenerational transmission of subsistence skills.